Proteins multi-funnel energy landscape and misfolding diseases - Cruzeiro, Leonor (2014)
The problem of how a given a-amino acid sequence, in cells, most of the times, assumes the native structure, is a fundamental problem in Biology, known as the protein folding problem. Here, evidence is presented that suggests that the same a-amino acid sequence can assume several, very different, structures that have the same Gibbs energy as the native structure, in the same thermodynamic conditions. These results lend support to a multi-funnel Gibbs energy landscape for proteins in which Anfinsen’s thermodynamic hypothesis alone cannot explain protein folding. How then do proteins fold? In a multi-funnel picture, transient deterministic forces are needed to select the native funnel from all other funnels that the protein can potentially fall into. The suggestion here is that such transient, deterministic forces arise from specific vibrational excited states (VES) that constitute the first step in protein folding and function (the VES hypothesis). An application of the VES hypothesis to calculate the energy absorbed, from water molecules, by a protein a-helix with extensive glutamine (gln) repeats is made, which can explain the structural instability of these proteins and their association with many misfolding diseases.